THE IMPLEMENTATION OF INTERNATIONAL TRADEMARK REGISTRATION IN INDONESIA POST-RATIFICATION OF MADRID PROTOCOL - Setiawan, Andry; Sulistyaningsih, Dewi; Aglesius, Leo Bernado (Varia Justicia, 2018)
In early October 2017, the Indonesian government, represented by the Directorate General of Intellectual Property of the Ministry of Justice and Human Rights, has officially ratified the Protocol Relating to the Madrid Agreement Concerning the International Registration of Marks (Madrid Protocol). The ratification is contained in the Presidential Regulation No. 92 of 2017 on Ratification of Protocol Relating to the Madrid Agreement Concerning the International Registration of Marks, 1989. The Presidential Regulation shall be the legal basis of enforcement that regulates the international trademark registration in Indonesia. The concept offered through the international trademark registration system based on the Madrid Protocol is its practicality which passes only one examination, one Language, one currency and it is integrated by the International Bureau administered by WIPO without changing the sovereignty of each member country which ratifies the system. The objective of this paper is to find out how the trademark registration is implemented based on the Madrid Protocol after its ratification in Indonesia and how the system will impact. The results of this paper will be beneficial for the public so that they know the mechanism of the international trademark registration and the impact of this system